2021
DOI: 10.1016/j.ijid.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric toxicity and cycloserine concentrations during treatment for multidrug-resistant tuberculosis

Abstract: Background: Cycloserine, or its structural analogue terizidone, has been associated with neuropsychiatric toxicity (psychosis, depression, and neuropathy). Prospective clinical data on the incidence of and risk factors for neuropsychiatric toxicity in TB patients treated with cycloserine are limited. Methods: A prospective evaluation of neuropsychiatric toxicity was performed using validated screening tools in patients with multidrug-resistant tuberculosis treated with terizidone. Cox proportional hazard model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Peripheral neuropathy is commonly associated with long-term use of LZD and less frequently with INH, CS and FQs. 72 , 77 These possible and serious AEs require patient and care provider awareness, as well as monthly peripheral neuropathy and vision assessment. Peripheral neuropathy in young children can be difficult to diagnose and signs may include refusal to bear weight or complaints of pain or irritability.…”
Section: Standardmentioning
confidence: 99%
“…Peripheral neuropathy is commonly associated with long-term use of LZD and less frequently with INH, CS and FQs. 72 , 77 These possible and serious AEs require patient and care provider awareness, as well as monthly peripheral neuropathy and vision assessment. Peripheral neuropathy in young children can be difficult to diagnose and signs may include refusal to bear weight or complaints of pain or irritability.…”
Section: Standardmentioning
confidence: 99%
“…In fact, it would have been interesting to see if the pathogenic effects attributed to D-cycloserine in a mouse model of Gaucher disease ( 98 ) could have been offset by pyridoxine coadministration. It is worth noting that administration of high doses of pyridoxine, with or without D-cycloserine administration, can lead to peripheral neuropathy ( 100 ), indicating that a carefully selected dose of pyridoxine is necessary.…”
Section: D-cycloserine–safety Considerationsmentioning
confidence: 99%
“…Cycloserine was discontinued and replaced in all studies. Indeed, several authors have reported the relative psychiatric toxicity of cycloserine [27][28].…”
Section: Serious Adverse Effectsmentioning
confidence: 99%